Determinants of first line antiretroviral therapy treatment failure among adult patients on ART at central Ethiopia: un-matched case control study - Mulisa, Diriba (BMC Infect Dis, 2019)
BACKGROUND: In 2018 in Ethiopia, magnitude of human immunodeficiency virus Acquired Immunodeficiency Syndrome treatment failure was 15.9% and currently the number of patient receiving second line antiretroviral therapy (ART) is more increasing than those taking first line ART. Little is known about the predictors of treatment failure in the study area. Therefore; more factors that can be risk for first line ART failure have to identified to make the patients stay on first line ART for long times. Consequently, the aim of this study was to identify determinants of first line ART treatment failure among patients on ART at St. Luke referral hospital and Tulubolo General Hospital, 2019. METHODS: A 1:2 un-matched case-control study was conducted among adult patients on active follow up. One new group variables was formed as group 1 for cases and group 0 for controls and then data was entered in to Epi data version 3 and exported to STATA SE version 14 for analysis. From binary logistic regression variables with p value ≤0.25 were a candidate for multiple logistic regression. At the end variables with a p-value ≤0.05 were considered as statistically significant. RESULT: A total of 350 (117 cases and 233 controls) patients were participated in the study. Starting ART after 2 years of being confirmed HIV positive (AOR = 3.82 95% CI 1.37,10.6), nevirapine (NVP) based initial ART (AOR = 2.77,95%CI 1.22,6.28) having history of lost to follow up (AOR 3.66,95%CI 1.44,9.27) and base line opportunistic infection (AOR = 1.97,95%CI 1.06,3.63), staying on first line ART for greater than 5 years (AOR = 3.42,95%CI 1.63,7.19) and CD4 less than100cell/ul (AOR = 2.72,95%CI 1.46,5.07) were independent determinants of first line ART treatment failure. CONCLUSION: Lost to follow up, staying on first line ART for greater than 5 years, presence of opportunistic infections, NVP based NNRT, late initiation of ART are determinant factors for first line ART treatment failure. The concerned bodies have to focus and act on those identified factors to maintain the patient on first line ART.